Uzupełnienie do artykułu o lokacjach osad wiejskich na prawie niemieckim w dawnych posiadłościach pabianickich należących do kapituły krakowskiej - Zajączkowski, Stanisław Marian (Acta Universitatis Lodziensis. Folia Historica, 2000)
In the regional „Pabianiciana” journal, vol. 3, my article concerned with the question mentioned above has appeared. In the text some deletions have been made without my approval or acknowledgement. In the typescript to be printed none my complements have been included. Consequently, in the present article I have accomplished all necessary corrections to the text published in the „Pabianiciana” journal, paying special attention to the problem of the „opole” nature as well as the question of the so called Pabianice land. Basing on more recent literature, I have also completed the question of the so called German law.